DIFFERENTIATED THYROID CANCER WITH POSITIVE ANTI-THYROGLOBULIN ANTIBODY AND FINDINGS OF DISEASE EVALUATION ON FDG PET-CT SCAN - Zanial, Ahmad Zaid; Arunasalem, Reana Devi; Hussain, Wan Muhd Anas Wan (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCITON Fluorodeoxyglucose positron emission tomographycomputerised tomography (FDG PET-CT) imaging has been advocated in differentiated thyroid cancer (DTC) cases with negative radioiodine scan but elevated serum thyroglobulin. Although there is limited available data, FDG PET-CT is also used to assess patients with progressively increasing anti-thyroglobulin antibodies (anti-TG). We aimed to determine characteristics of anti-TG positive DTC patients referred for FDG PET-CT and their association with abnormal imaging findings. METHODOLOGY We performed a cross-sectional retrospective study of all DTC patients with positive anti-TG who were managed with radioiodine therapy in our institution and referred for FDG PET-CT. Those who defaulted on the PET-CT appointment and clinic follow up with incomplete documentation were excluded. Baseline nodal disease and metastasis were determined following the first radioiodine therapy. RESULT Majority were females (70.8%). Mean values for age and cancer duration were 51.29 and 7.13 years respectively. Papillary thyroid carcinoma was predominant (95.8%). Majority had baseline nodal involvement (87.5%); a quarter had detectable distant metastasis. Most patients underwent less than five sessions of radioiodine therapy (83.3%). Majority had negative radioiodine scan prior to PETCT (87.5%). Cases of positive residual radioiodine-avid disease showed lower mean values of anti-TG compared to those with negative radioiodine scan (1423 vs. 4671 IU/ mL, p <0.05). FDG-avid malignant disease was observed in 62.5%; three patients were considered to have mixed disease following the PET-CT assessment. Female gender and those with baseline nodal involvement were found to be significantly associated with FDG-avid disease (p <0.05). CONCLUSION FDG PET-CT has an important role in evaluating DTC patients with positive anti-TG. Those with negative radioiodine scan had higher mean values of anti-TG. Females and patients with baseline nodal involvement were associated with FDG-avid disease.